Development of a hybrid circuit for a system (solar – wind-hydraulic) - مصطفى المرمور; صلاح داوود; محمد خير محمد (Latakia University Journal -Engineering Sciences Series, 2023)
Solar and wind energy are clean energy sources with great potential to reduce dependence on the grid. The research aims to study a circuit consisting of three systems (wind turbine - electric solar cells - hydraulic) to supply electrical loads to homes and operate pumps. Where the average wind speed is 4 m/s at a height of 30 m. The average daily solar radiation intensity for the months of the year was studied at several values ​​of the angle of inclination of the solar panel. It was found that the optimal angle of inclination of the solar panel is the angle corresponding to the latitude angle of the studied area, and the capacity and number of solar cells were studied. The hydraulic losses inside the pipes were studied in order to know the capacity of the pump needed to be installed to overcome the losses. The three systems were modeled in the Matlab/simulink environment and linked with an electrical power control controller that extracts energy from the wind and solar systems and distributes it to the consumer, batteries and pump.